Strength training for children and adolescents - Guy, J. A.; Micheli, L. J. (Journal of the American Academy of Orthopaedic Surgeons, 2001)
Strength, or resistance, training for young athletes has become one of the most popular and rapidly evolving modes of enhancing athletic performance. Early studies questioned both the safety and the effectiveness of strength training for young athletes, but current evidence indicates that both children and adolescents can increase muscular strength as a consequence of strength training. This increase in strength is largely related to the intensity and volume of loading and appears to be the result of increased neuromuscular activation and coordination, rather than muscle hypertrophy. Training-induced strength gains are largely reversible when the training is discontinued. There is no current evidence to support the misconceptions that children need androgens for strength gain or lose flexibility with training. Given proper supervision and appropriate program design, young athletes participating in resistance training can increase muscular strength and do not appear to be at any greater risk of injury than young athletes who have not undergone such training.